Fabrication of centimeter-scale light-emitting diode with improved performance based on graphene quantum dots. (14th February 2017) - Xu, Chang; Yang, Siwei; Tian, Linfan; Guo, Tianqi; Ding, Guqiao; Zhao, Jianwei; Sun, Jing; Lu, Jian; Wang, Zhongyang
Abstract: The low solubility of graphene quantum dots in organic solvents limits their application in optoelectronic devices. We propose a bottom-up synthesis approach that yields graphene quantum dots that can be dissolved in organic solvents, and we apply this approach to construct new devices. Further, by using the newly designed structure described here, a centimeter-scale emitting area and a maximum external quantum efficiency of approximately 1.2% are achieved. The method we propose provides a feasible way to develop light-emitting diodes based on graphene quantum dots for practical application.